2016
DOI: 10.24842/1611/0011
|View full text |Cite
|
Sign up to set email alerts
|

Photo Catalytic Degradation of Methylene Blue by Using CuO Nanoparticles

Abstract: Photo catalytic degradation of methylene blue has been studied by using different concentration from CuO nanoparticles. The study was carried out with sunlight and in the absence of UV source. As well as the study was the presence of UV source. The Characterization catalysts have performs by UV-Visible spectroscopy. The rate of degradation of dye was monitored spectra photo metrically by measuring absorbance of dye at regular time intervals, change the concentration of dye and change the concentration of catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…In this study, the phytosynthesized CuONPs in sizes between 90 and 250 nm showed good decolorization efficiency; however, some other studies synthesized relatively smaller sized CuONPs were reported higher percentage of decolorization [37, 38]. Our results are advanced in terms of being faster and an increased level of decolorization when compared with previous reports [28, 39]. These results represent that CuONPs have a good dye decolorization activity on Brilliant Blue R‐250.…”
Section: Resultssupporting
confidence: 43%
“…In this study, the phytosynthesized CuONPs in sizes between 90 and 250 nm showed good decolorization efficiency; however, some other studies synthesized relatively smaller sized CuONPs were reported higher percentage of decolorization [37, 38]. Our results are advanced in terms of being faster and an increased level of decolorization when compared with previous reports [28, 39]. These results represent that CuONPs have a good dye decolorization activity on Brilliant Blue R‐250.…”
Section: Resultssupporting
confidence: 43%
“…All samples were machined as half bush. The important properties of the main materials used in the wear tests were shown in table (1). Each sample was first polished and cleaned using acetone before wear test.…”
Section: A Samples Preparationmentioning
confidence: 99%
“…hen the components of machinery move in contact with one another, natural wear process take place which results in the removal of wear material from surfaces [1][2][3]. The free material may be transported in the lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…An effective way to increase polymers’ refractive index is by introducing high n inorganic nanoparticles into the organic polymers. Recently, doping with TiO 2 [ 11 , 12 ], ZnO [ 13 , 14 ], ZnS [ 15 ], ZrO 2 [ 16 ], Al 2 O 3 [ 17 ] NPs, and so on, has been utilized to obtain nanocomposites of high optical quality for nanomaterial applications [ 18 , 19 ]. These nanocomposites can be exploited in CL manufacturing.…”
Section: Introductionmentioning
confidence: 99%